2008
DOI: 10.1007/s11240-008-9415-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different liquid/solid culture systems in the production of somatic embryos from Narcissus L. ovary explants

Abstract: Alternative procedures for the production of Narcissus L. somatic embryos were investigated. Somatic embryogenesis was initiated on ovary explants isolated from cv. Carlton bulbs, chilled for 12 weeks at 5°C. The explants were cultured on MS media with 3% sucrose and growth regulators: Picloram or 2,4-D (10 or 25 lM) and BA (1 or 5 lM) for 12 weeks in the culture systems: continuous cultivation on solid media, continuous cultivation in liquid media and sequential cultivation using cycles in liquid and solid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The developed embryogenic calli of C. australis were multiplied on initial media, similarly to Panicum maximum (Chen et al, 2006), or Narcissus L. 'Actea' (Malik, 2008). In our experiment, an increase in the biomass of embryogenic callus depended on the type and concentration of auxin.…”
Section: Growth Regulators (M)mentioning
confidence: 50%
“…The developed embryogenic calli of C. australis were multiplied on initial media, similarly to Panicum maximum (Chen et al, 2006), or Narcissus L. 'Actea' (Malik, 2008). In our experiment, an increase in the biomass of embryogenic callus depended on the type and concentration of auxin.…”
Section: Growth Regulators (M)mentioning
confidence: 50%
“…In contrast, our results showed that embryogenic callus could not be induced from tTCLs of bulblet microscales cultured in the dark on MS medium containing NAA and TDZ in L. ledebourii (data not shown), while embryos showing a bipolar structure were developed in the presence of NAA or in combination with BA. Similarly, the combination of an auxin and BA has been used to initiate somatic embryos in other rhizomatous and bulbous ornamental crops, such as Alstroemeria (Kim et al 2006), Iris (Shibli and Ajlouni 2000), Narcissus (Selles et al 1999;Malik 2008), and Tulipa (Ptak and Bach 2007).…”
Section: Induction Of Sementioning
confidence: 99%
“…A number of studies have reported that Gal is accumulated in Amaryllidaceae tissue cultures and that some factors can enhance its accumulation (Selles et al 1997;Colque et al 2004;Diop et al 2007;Diop et al 2006;Ptak et al 2009;Georgiev et al 2009;Berkov et al 2009a, b;Ptak et al 2010), suggesting that biotechnological methods can be considered as an alternative approach for the production of this alkaloid. Changes in the external conditions of cultures strongly affect alkaloid metabolism in plant cell and tissue cultures (Mantell and Smith 1983), but they also affect regeneration from somatic embryos (Malik 2008). Sucrose is an essential and the most common carbon source used in plant cell tissue and organ culture media.…”
Section: Introductionmentioning
confidence: 99%